Integrating conservation and development : community participation in ecotourism projects : an investigation into community participation in ecotourism development projects in order to ensure the integration of protected area conservation and rural development, with particular reference to a case study at Cathedral Peak in the Natal Drakensberg Park - Theron, Izak Petrus (Department of Environmental and Geographical Science, 2016)
This study arises out of a proposal of the Natal Parks Board (NPB) to develop a 200 bed hutted camp at Cathedral Peak in the Natal Drakensberg. In line with the NPB's stated commitment to the principles of Integrated Environmental Management (IEM), a multidisciplinary group, comprising five students from the Masters programme of the Department of Environmental and Geographical Sciences of the University of Cape Town, was commissioned to conduct a Preliminary Environmental Impact Assessment (PEIA) on the proposed development. The author was one of the members of this study team, hereafter referred to as the Masters Group, which conducted the PEIA at Cathedral Peak under the supervision of the Environmental Evaluation Unit of the University of Cape Town.